Case Series: A Kindred With Eruptive Vellus Hair Cysts and Systemic Features. Issue 3 (November 2017) - Ponzo, Marisa G.; Van Allen, Margot I.; Armstrong, Linlea; Martinka, Magdalena; Dutz, Jan P.
Eruptive vellus hair cysts (EVHCs) often occur on the trunk and limbs. Facial involvement is uncommon. Autosomal dominant inheritance has been described, but associated extracutaneous anomalies have not. We describe a 4-patient kindred presenting with multiple facial EVHCs and an association of preauricular pits, lipomas, joint hypermobility, and cardiac defects. Histopathologic examination confirmed the diagnosis of EVHCs in 3 affected individuals. We propose that facial EVHCs may indicate the presence of an inherited autosomal dominant disorder with extracutaneous manifestations. Extracutaneous manifestations noted in the kindred have been sporadically described in association with steatocystoma multiplex (SM), a condition occasionally noted in the presence of EVHCs, further supporting an association between these disorders.